2012
DOI: 10.1097/olq.0b013e31826ef2da
|View full text |Cite
|
Sign up to set email alerts
|

Oral Human Papillomavirus and Human Herpesvirus-8 Infections Among Human Immunodeficiency Virus Type 1–Infected Men and Women in Italy

Abstract: High prevalence of oral HPV and HHV8 infections was observed; MSM had the highest figures, despite better control of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…Although the 19.5% prevalence for oral HPV infection was higher than previously reported for HIV-uninfected youth [Summersgill et al, 2001;Smith et al, 2004;Fakhry et al, 2006;D'Souza et al, 2007;Smith et al, 2007;Kreimer et al, 2010Kreimer et al, , 2011Beachler et al, 2012;Gillison et al, 2012;Kero et al, 2012;Pickard et al, 2012;Paolini et al, 2013], it was similar to that among youth at high-risk for sexually transmitted infections [Du et al, 2012;Schlecht et al, 2012]. The oral EBV prevalence (88.2%) in our study population was consistent with estimates previously reported in HIV-infected adults (42.1-90%) [Ammatuna et al, 2001;Miller et al, 2006], and healthy adults (90%) [Ikuta et al, 2000], and KSHV prevalence (11.8%) was also consistent with prior reports (11.6-57%) [Widmer et al, 2006;de Franca et al, 2011;Del Mistro et al, 2012].…”
Section: Discussionsupporting
confidence: 91%
“…Although the 19.5% prevalence for oral HPV infection was higher than previously reported for HIV-uninfected youth [Summersgill et al, 2001;Smith et al, 2004;Fakhry et al, 2006;D'Souza et al, 2007;Smith et al, 2007;Kreimer et al, 2010Kreimer et al, , 2011Beachler et al, 2012;Gillison et al, 2012;Kero et al, 2012;Pickard et al, 2012;Paolini et al, 2013], it was similar to that among youth at high-risk for sexually transmitted infections [Du et al, 2012;Schlecht et al, 2012]. The oral EBV prevalence (88.2%) in our study population was consistent with estimates previously reported in HIV-infected adults (42.1-90%) [Ammatuna et al, 2001;Miller et al, 2006], and healthy adults (90%) [Ikuta et al, 2000], and KSHV prevalence (11.8%) was also consistent with prior reports (11.6-57%) [Widmer et al, 2006;de Franca et al, 2011;Del Mistro et al, 2012].…”
Section: Discussionsupporting
confidence: 91%
“…Of notice, a high frequency of HHV‐8 infection was observed among MSM, compared to previous studies that reported a frequency ranging from 6% to 32.4% [Pierrotti et al, 2005; Ishak de et al, ; Batista et al, ]. This association is related to a greater number of sexual partners and a history of ISTDs [Mistro et al, ]. Although, it seems pertinent to observe that in sexual encounters it is difficult to exclude the possibility of behaviors that involve an oral route, such as oral sex which presented a borderline significance.…”
Section: Discussionmentioning
confidence: 80%
“…However, data reported on heterosexual HIV-infected men are scarce [10,11]. The purpose of this study is to present data on the prevalence, evolution (clearance and incidence) and risk factors associated with type-specific HPV infections in the oral mucosa of MSM and heterosexual HIV-infected men.…”
Section: Regular and Careful Oral Inspection Is Neededmentioning
confidence: 98%